Implications of vitrinite-reflectance suppression for the tectonic and thermal history of the Malay Basin - Waples, Douglas W. (Geological Society of Malaysia, 1995)
Vitrinite-reflectance profiles for wells in the Malay Basin are generally consistent, and appear at first glance to accurately represent present-day thermal maturities. However, these measured Ro values are much lower than one would expect for wells with such high present-day geothermal gradients. Consequently, calculated Ro values can only be fitted to the measured Ro data by proposing a strong and recent heat pulse. In this scenario, the paleoheat flow was much lower than the present heat flow, and rose to the present levels within the last few million years or less. A plausible tectonic history for the Malay Basin can be constructed that justifies this scenario, because Quaternary volcanic and hot springs are known, and because the last 10 million years has seen renewed subsidence after a period of uplift during the Middle Miocene. However, FAMM (Fluorescence Alteration of Multiple Macerals) data obtained from seven wells indicate that the measured Ro values are much too low in most of the Malay Basin. Ro values have been suppressed by the presence of abundant liptinite and perhydrous vitrinite, probably as a result of marine influence, except along the western margin of the basin and in the far northwestern end. Calibration of the paleoheat flow with FAMM data permits use of a much more constant thermal history at each location. In this model, the main heat flow increased during Oligocene rifting in proportion to the amount of crustal extension, and then has subsequently decayed exponentially to modern levels. Using this paleoheat flow model, hydrocarbons are generated much earlier and maturities in the basin are much higher than if the paleoheat flow model is calibrated using the measured Ro data. These conclusions in turn indicate that the recent tectonic history of the Malay Basin has probably been rather gentle, in keeping with evidence from sedimentation rates. Although we are not yet certain how common vitrinite suppression is globally or in the Malay Basin, these results indicate that (1) all data sets should be routinely checked for vitrinite suppression, especially in areas where the phenomenon has been recognized; (2) any thermal model requiring a significant recent heat pulse to match measured and calculated Ro values should be viewed with suspicion until validated independently; and (3) errors in reconstruction of thermal and tectonic history can often lead to significant errors in exploration decisions.